Reflecting on Diversity and Gender Equality in Artificial Intelligence in Africa - Helen Titilola Olojede (The Thinker)
Many ethical issues plague the field of AI, and several ethical solutions, mainly from the Global North, have been proposed. Among the issues inherent in ethical AI are bias and lack of diversity. Openair Africa reports, for example, an enormously low participation/visibility of women in today’s digital world. World Economic Report states that worldwide, only about 22% of women are in the field of artificial intelligence compared to 78% of men. In the 2022 Cybersecurity Workforce Report, women account for just 24%. The 2020 Gender Equality Index: Digitalisation and Future of Work also indicates that only one out of two women, 54%, perceive robots and AI positively compared to 67% of men. Thus, this paper discusses diversity and gender equality in AI from the African context. How should we safeguard AI systems from rehashing extant inequality? To what extent can we ensure AI eliminates bias and fosters equality? To this end, this paper proposes a communal approach to the conception, design, development, and deployment of AI systems to address this abysmal situation towards a gender-smart and truly inclusive AI in Africa.